Impact of novel therapies for mantle cell lymphoma in the real world setting: a report from the UK's Haematological Malignancy Research Network (HMRN). (13th March 2018) - Smith, Alexandra; Roman, Eve; Appleton, Simon; Howell, Debra; Johnson, Rod; Burton, Cathy; Patmore, Russell
Summary: The treatment landscape for mantle cell lymphoma (MCL) has changed dramatically in recent years, with findings from clinical trials reporting improvements in survival. Data on the general patient population are, however, sparse; and it is unclear whether the effects observed in clinical trials have translated into the real‐world setting. To investigate this, we examined first‐line and relapsed/refractory (RR) disease management in 335 MCL patients diagnosed between 2004 and 2015 in an established population‐based patient cohort, along with data on demographic, diagnostic and prognostic factors. Marked treatment and survival changes were observed; first‐line rituximab immunotherapy, for example, increased from 32% to 86% over the 11‐year period, and median survival increased from 2·0 years among those first treated in 2004–2011 to 3·5 years among those treated in 2012–2015. Outcomes for RR disease also improved, from 8 months in 2004–2011 to 16·8 months in 2012–2015, coinciding with the introduction of agents, such as bendamustine and ibrutinib. Encouragingly, improvements were seen across all ages; 1‐year overall survival among patients over 70 years treated for RR disease almost doubled. Our analyses underscore the importance of monitoring the impact of treatment changes in the real‐world setting.